Necessary Third Parties: Multidisciplinary Collaboration and Inadequate Professional Privileges in Domestic Violence Practice - Baker, Jeffrey R. (Columbia Journal of Gender and Law, 2011)
The rise of multidisciplinary practices among public- interest lawyers and other professionals promotes more effective and thorough services for vulnerable clients. Attorneys, counselors, social workers and others are recognizing that clients may present issues that transcend the scope and purpose of a single profession. In various forms, these professionals create formal or ad hoc partnerships as they minster to whole clients, not just to a client’s peculiar, momentary problem. For victims of domestic violence, these collaborations can yield more successful outcomes and fruitful service, can be necessary for competent representation, and may even be critical to her very survival. As the client works to escape a violent and oppressive relationship, her diverse professional servants must address the acute conflation of legal, medical, psychological, emotional and financial crises that beset her.